2009
DOI: 10.1037/a0016502
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a marijuana expectancy manipulation: Piloting the balanced-placebo design for marijuana.

Abstract: Although alcohol and nicotine administration studies have demonstrated that manipulating subjects' expectancies regarding drug content affects drug response, research with marijuana has not adequately studied drug expectancy effects. The present pilot study was the first to evaluate the credibility and effect of expectancy manipulation on subjective measures and smoking patterns using a marijuana administration balanced-placebo design (BPD). In a 2 × 2 instructional set (told delta-9-tetrahydrocannabinol [THC]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 63 publications
1
76
0
Order By: Relevance
“…Findings from these studies using the open/hidden drug paradigm are supported by investigations that explicitly modulated the expectancy concerning a given drug by verbal instructions (Lyerly et al, 1964;Kirk et al, 1998;Metrik et al, 2009). The detrimental influence of negative expectations on the drug response became, for instance, apparent in a behavioral experimental study by Dworkin et al (1983), who reported a reversal of 716 analgesia by nitrous oxide in dental pain when participants expected the drug to increase awareness of bodily sensations.…”
Section: The Effect Of Placebo Responses On Pharmacological Treatmentioning
confidence: 51%
“…Findings from these studies using the open/hidden drug paradigm are supported by investigations that explicitly modulated the expectancy concerning a given drug by verbal instructions (Lyerly et al, 1964;Kirk et al, 1998;Metrik et al, 2009). The detrimental influence of negative expectations on the drug response became, for instance, apparent in a behavioral experimental study by Dworkin et al (1983), who reported a reversal of 716 analgesia by nitrous oxide in dental pain when participants expected the drug to increase awareness of bodily sensations.…”
Section: The Effect Of Placebo Responses On Pharmacological Treatmentioning
confidence: 51%
“…This phenomenon is not restricted to analgesics, because similar effects have also been reported for treatments in other medical conditions (13). For instance, expectation increases the anxiolytic effects of diazepam in postoperative anxiety, the effect of deep brain stimulation of the subthalamic nucleus on motor performance in Parkinson's disease, and the subjective responses to psychotropic drugs such as D 9 -tetrahydrocannabinol (11,15) or methylphenidate (23).…”
Section: Discussionmentioning
confidence: 87%
“…Those who anticipate that the plant will create a positive outcome tend to use more than those who expect otherwise (Hawkins 2007;Metrik et al 2009;Skenderian et al 2008;Vangsness, Bry & LaBouvie 2005). These results suggest that standard expectancy theories of marijuana use might apply to a self-medication hypothesis of marijuana consumption for PTSD symptoms.…”
mentioning
confidence: 70%